2020
DOI: 10.1109/access.2020.2976732
|View full text |Cite
|
Sign up to set email alerts
|

Transmit Antenna Selection for Precoding-Aided Spatial Modulation

Abstract: This paper examines the impacts of transmit antenna subset (TAS) selection on the biterror-rate (BER) performance of linear precoding-aided spatial modulation (PSM) multiple-input multipleoutput (MIMO) systems. It is analytically shown that decreasing the number of active transmit antennas by TAS selection, which can be used to reduce the number of RF units at the transmitter side, always degrades the BER performance. The expression of a received signal-to-noise ratio (SNR) loss is also derived and its analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…The ZF and minimum mean square error precoding methods are commonly used in PSM. To be consistent with the previous works for the PSM systems [7], [8], [10], [11] and [18], we utilize the ZF precoding scheme in this paper. Then the ZF precoding matrix is given as  .…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The ZF and minimum mean square error precoding methods are commonly used in PSM. To be consistent with the previous works for the PSM systems [7], [8], [10], [11] and [18], we utilize the ZF precoding scheme in this paper. Then the ZF precoding matrix is given as  .…”
Section: Introductionmentioning
confidence: 77%
“…RAS selection has been studied for the PSM systems [21]- [23]. In [18], the effects of only TAS selection on the bit error rate (BER) performance of the zero-forcing (ZF)-based PSM systems have been investigated. In [20], two TAS selection schemes with lowcomplexity have been developed for the PSM systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the above article [1], the authors found some mistakes in real summation (RS) computations. As the computational complexity in terms of real summation (RS) is re-evaluated in the revision process, we didn't consider 2 RSs additionally required for a complex multiplication.…”
mentioning
confidence: 99%